The odd one in: re-diagnosis and phylogenetic placement of the Assam Day Gecko, Cnemaspis assamensis Das & Sengupta 2000 (Squamata: Gekkonidae) - Sengupta, Shruti; Purakayasta, Jayaditya; Anandan, Nitesh; Das, Madhurima; Chan, Kin Onn; Murthy, Channakesava (Zootaxa, 2021)
Herein we provide new information on Cnemaspis assamensis, the only species of Cnemaspis known from north-eastern India. Based on five new samples, morphological parameters are described. The species was found to have pre-cloacal and femoral pores, not accounted for in the original description. Genetic assessment of the species was made using a 914 bp fragment of the ND2 mitochondrial gene and the species was recovered as the sister taxon of the C. podihuna clade from Sri Lanka.